The Efficacy and Safety of Tetrachlorodecaoxide in Comparison with Super-oxidised Solution in Wound Healing - Parikh, Romil; Bakhshi, Girish; Naik, Madhushree; Gaikwad, Bhargav; Jadhav, Kavita; Tayade, Mukund (Archives of Plastic Surgery, 2016)
Background Some of the relatively newer, more efficacious, and potent topical wound dressing solutions include tetrachlorodecaoxide and super-oxidised solution. This study compares the efficacy and safety of these two drugs.Methods This is a block-randomised, double blind, parallel-arm, post-marketing study. One hundred fifty patients with ulcers (75 blocks uniform for sex, ulcer aetiology, diabetes mellitus, and wound area score) were randomised into the two treatment arms. Patients were observed for eight weeks with weekly assessments. One hundred and twenty patients completed the study. Wound healing was objectively assessed by measurement of wound area, scoring of wound exudation and tissue type, and using the pressure ulcer scale of healing Tool (validated for multiple wound aetiologies). Subjective improvement in pain was noted using a visual analogue scale. Both groups were compared using Mann–Whitney U test on all indicators.Results Difference in change in wound tissue type in the two groups was significant (α=0.05) by intention-to-treat (ITT) and per-protocol (PP) analysis at the end of week two (ITT and PP, P<0.001) and week four (ITT, P=0.010; PP, P=0.009). P-values for other comparisons were not significant (P>0.05). No study-related adverse events were observed.Conclusions Both drugs are efficacious. Tetrachlorodecaoxide yields healthy granulation tissue earlier. Both drugs appear to be safe for application.
Keywords: Tetrachlorodecaoxide; Superoxidized water; Ulcer; Wound healing